(untitled) (Research, Society and Development, 2022)
The present study sought to identify management difficulties or a lack of knowledge regarding the use of the bag-valve-mask (BVM) device among intensive care professionals. The process took place in four stages, the first with the application of a structured questionnaire that addressed basic questions, such as knowledge of the device, the second through a practical test, where participants simulated a routine care, to assess pressure and volume. carried out by the same, then the third phase occurs with a continuing education based on the difficulties presented by the volunteers during the execution of the tests, the fourth and last, consists of a theoretical post test, for analysis of the learning fixation. Intensivists have, for the most part, practical mastery over equipment, this is observed because they generate pressures at safe levels, tidal volume with an average of 7.57±2.95 ml, being within the estimated ideal and respiratory rate of 40.87 ±15.78 incursions per minute, also as recommended. In the theoretical evaluation, it was possible to indicate few difficulties, the one that stands out the most is 48.4% say they do not know the ideal pressure to be performed on a stable neonate. It is worth emphasizing the importance of continuous theoretical and practical training in any hospital setting. The prepared professional avoids harm to the patient, performs his function and provides a service safely, providing humanized care, reducing expenses and hospitalization period.